E-banking Services on Financial Performance of Financial Institutions:A Case of Diamond Trust Bank Mbale Branch - Olinga Ronald (Uganda Christian University, 2024)
The general objective of the study was to examine the effect of e-banking services on financial performance of Diamond trust Bank. The study was guided by the following objectives: to establish the effect of Mobile financial information on financial performance of Diamond trust Bank; to assess the effect of mobile transfers and receipts on financial performance of Diamond trust Bank and to assess the effect of online banking on financial performance of Diamond trust Bank. A case study research design was used. The study predominantly employed a quantitative approach but also used a qualitative approach. The study population consisted of 40 participants. A sample size of 36 respondents was selected using simple and purposive sampling techniques. Quantitative data analysis mainly consisted of descriptive statistics (percentages) and inferential statistics (Spearman correlation, coefficient of determination regression). Content analysis was used to analyze qualitative data. Findings revealed that there is a significant effect of Mobile financial information on financial performance of Diamond trust bank. Secondly, there is a significant effect of mobile transfers on financial performance of Diamond trust bank. Lastly, findings indicated that online banking has a positive relationship with financial performance of Diamond trust Bank. It was concluded that e-banking services variables (Mobile financial information services, mobile transfers and online banking) positively influenced financial performance of Diamond trust Bank but not online banking. Thus, it was recommended that for purposes of promoting Mobile financial information services towards financial performance, trust building among the customers should be a major concern for Diamond trust Bank while improving the usefulness of e-banking services. In order to achieve more with mobile transfers on financial performance, it is imperative that Diamond trust Bank ensures security and privacy are in place to monitor and evaluate the usage of the implemented technologies. Lastly, on online banking on financial performance of Diamond trust Bank, the bank needs to make sure that awareness about online banking is created in the public through massive advertisement on radios, televisions and newspapers.